Keiretsu inside the hidden japanese conglomerates - Miyashita, Kenichi; Russel, David w. (McGraw-Hill, 1994)
Maverick capitalist Boone Pickens has denounced them as "government-sponsored cartels." Chrysler's Lee lacocca has suggested forming "our own little keiretsu system" in the United States. But whether you regard Japan's mammoth corporate alliances as a menace to trade or a model for change, you probably don't understand how the keiretsu really operate. Here, at last, is the book that will open your eyes. "Our hard-nosed business leaders look like Dorothy wandering through Oz when it comes to dealing with Japan," observes David Russell, an American business journalist based in Tokyo since 1982. In these pages, he and Japanese counterpart Kenichi Miyashita reveal the inner workings of the keiretsu. Their unbiased, readable investigation delivers a wealth of information about the system as a whole, its individual members, and the intricate web of relationships that links banks, manufacturers, suppliers, distributors, and the Japanese government